Spatially optimized 125I brachytherapy: a novel immunomodulatory approach based on spatially fractionated radiation therapy principles - Sun, Qiyu; Hu, Yanbo; Sun, Zhiqian; Du, Lulu; Huang, Rui; Wang, Lichao; Cui, Zhenzhen; Yang, Jiaxin; Ma, Xiaowen; Li, Min (Frontiers in Oncology, 2025)
Conventional ¹²5I brachytherapy, emphasizing uniform dose coverage, may limit its potential to activate anti-tumor immunity. We propose integrating the principles of Spatially Fractionated Radiotherapy (SFRT) into ¹²5I brachytherapy. Through a heterogeneous dose design featuring “co-existing high- and low-dose regions”, this approach aims to synergize immunogenic cell death (ICD) with the preservation of immune cell function, thereby transforming the tumor into an “in situ vaccine”. The inherent characteristics of ¹²5I sources – namely, the steep dose gradient of their low-energy gamma rays and continuous low-dose-rate delivery – provide unique advantages for the precise construction of distinct regions: a high-dose zone (to induce ICD) and a low-dose zone (to support immune cell survival).We have established a novel dose evaluation framework (incorporating metrics such as HDRI [High-Dose Region Index], LDRI [Low-Dose Region Index], DGUI [Dose Gradient Utilization Index], and SHS [Spatial Heterogeneity Score]) to replace traditional homogeneous indices like D90/V100. Furthermore, we present optimization strategies for parameters including source spacing and source activity. Finally, we systematically outline an integrated preclinical-to-clinical research pathway for combination with immunotherapy. This lays the theoretical and experimental foundation for developing tumor-type-specific, personalized treatment protocols based on the “¹²5I-SFRT + Immunotherapy” approach.